EFFECT OF PARITY AND SEASON OF CALVING ON SOME PRODUCTIVE AND REPRODUCTIVE TRAITS OF FRIESIAN COWS - Muthanna Al-Juwari; Mohammed S. M. Al-Salami (Mesopotamia Journal of Agriculture)
The study included analyzed 131 records belong to 34 Friesian cows reared at AL- Iśhagi dairy cattle station (50 km north of Baghdad) for the period from 1996 to 2005. The overall mean of the studied traits  milk yield 305 day (MY305day), lactation period (LP) , dry period (DP) the period between calving and first estrous (PSC), services per conceptions (SPC), day open (DO) ,gestation period (GP) and calving interval (CI) were 2775.81 kg, 315.30 days, 71.92 days, 65.52 days, 2.83 services, 109.47 days, 277.75 days, 390.53 days, respectively. Parity showed a significant effect on (MY305day), (LP), (SPC), (DP), but there was no significant effect for the other traits. Season of calving had a significant effect on(MY305day), (LP) and (CI) only. Cows calving through spring and autumn produced more milk significantly compared with cows calving in summer. (LP) and(CI)  was longer for cows calving in spring and shorter for there calving in autumn.